2020
DOI: 10.1177/0218492320932074
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ST-elevation myocardial infarction with failed thrombolysis

Abstract: Background Fibrinolytic therapy is an important reperfusion strategy, especially when primary percutaneous coronary interventions cannot be offered to ST-elevation myocardial infarction patients. Given that failed reperfusion after fibrinolytic therapy is common, it is pragmatic that the predictors, outcomes, and angiographic profiles of patients with failed thrombolysis are carefully scrutinized. Methods We prospectively studied clinical variables and outcomes over 30 months in 243 ST-elevation myocardial inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 20 publications
3
15
0
Order By: Relevance
“…The infarct-related artery in FT usually has persistent occlusion, where TIMI 3 flow (normal flow that fills the distal coronary bed) is not achieved. In one study, only 83.2% and 6.4% of STEMI patients with successful thrombolysis and FT, respectively, achieved the TIMI 3 flow [ 19 ]. In a meta-analysis, only TIMI 3 flow post thrombolysis is associated with a mortality benefit, with short-term mortality (in-hospital or 30-day mortality) of 3.7%, 7.0% and 8.8% among STEMI patients who achieved TIMI flow grade 3, 2, and 0/1, respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The infarct-related artery in FT usually has persistent occlusion, where TIMI 3 flow (normal flow that fills the distal coronary bed) is not achieved. In one study, only 83.2% and 6.4% of STEMI patients with successful thrombolysis and FT, respectively, achieved the TIMI 3 flow [ 19 ]. In a meta-analysis, only TIMI 3 flow post thrombolysis is associated with a mortality benefit, with short-term mortality (in-hospital or 30-day mortality) of 3.7%, 7.0% and 8.8% among STEMI patients who achieved TIMI flow grade 3, 2, and 0/1, respectively [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…We identified that STEMI patients with Killip II-IV at presentation to ED is a predictor of FT in the streptokinase arm but not in the tenecteplase arm, suggesting that tenecteplase is a better option in this population. Conversely, another Indian study has reported Killip II-IV as one of the predictors of FT in STEMI patients receiving either streptokinase or tenecteplase [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thrombolytic and interventional therapies based on the principle of vascular recanalization have been widely applied in clinical practice, in which great progress has been made [ 23 ]. However, severe ischemia-reperfusion injury, failure of myocardial cell regeneration, hypofunction of the heart, and even the immediate induction of heart failure are still vital factors for the high recurrence rate and mortality of MI, restricting the use of existing methods in the treatment of MI [ 18 ]. Based on the data of existing research, we found that the current therapy using bone marrow mesenchymal stem cell reduced the area of MI and improved heart function [ 13 ].…”
Section: Introductionmentioning
confidence: 99%